Rediscovery and description of a new species of Losgna (Cameron 1903): reviving a forgotten ichneumonid genus in India - Chaudhary, Karmannye Om; Reinisch, Sophia (Zootaxa, 2025)
The Darwin wasp genus Losgna (Cameron, 1903) (subfamily Ichneumoninae), is poorly documented in India, with no new species described since Heinrich’s work in 1965. Here we rediscover the genus in India and describe a new species collected from an urban dry scrub forest in Chandigarh. A taxonomic key for the identification of Indian Losgna is provided along with the illustrations of the new species and Generitype. The study significantly extends the known distribution of Losgna in the Oriental region and highlights the under-explored diversity of Ichneumoninae in India and the need for further taxonomic research.